2011
DOI: 10.1111/j.1468-2494.2011.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Penetration pattern of rhodamine dyes into enamel and dentin: confocal laser microscopy observation

Abstract: Enamel and dentin are susceptible to extrinsic and intrinsic stains. The purposes of this study were to determine the penetration pattern of Rhodamine B and dextran-conjugated Rhodamine B into the enamel and dentin as observed by confocal laser microscopy and to relate it to the penetration pattern of hydrogen peroxide commonly used as an active ingredient in tooth-whitening agents and high-molecular-weight staining molecules. Eighteen recently extracted human maxillary anterior teeth were used. Teeth were cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 14 publications
0
20
0
7
Order By: Relevance
“…Tooth whitening is based on the premise that hydrogen peroxide penetrates into the enamel and dentin to interact with the organic chromophores. It is well known that the dental hard tissues are highly permeable to fluids, and that the greatest fluid flow in the enamel and dentin is in the interprismatic spaces and dentinal tubules, respectively . Therefore, enamel and dentin are expected to act as semipermeable membranes and that they allow hydrogen peroxide to move according to Fick's second law of diffusion, which describes that the diffusion of a molecule is proportional to the surface area, diffusion coefficient, and concentration, and that it is inversely proportional to the diffusion distance …”
Section: Diffusionmentioning
confidence: 99%
“…Tooth whitening is based on the premise that hydrogen peroxide penetrates into the enamel and dentin to interact with the organic chromophores. It is well known that the dental hard tissues are highly permeable to fluids, and that the greatest fluid flow in the enamel and dentin is in the interprismatic spaces and dentinal tubules, respectively . Therefore, enamel and dentin are expected to act as semipermeable membranes and that they allow hydrogen peroxide to move according to Fick's second law of diffusion, which describes that the diffusion of a molecule is proportional to the surface area, diffusion coefficient, and concentration, and that it is inversely proportional to the diffusion distance …”
Section: Diffusionmentioning
confidence: 99%
“…It is worth noting that the precise mechanism of the molecular staining of enamel was uncertain at first, although as demonstrated by Kwon et al . () rhodamine can penetrate enamel deeply even without demineralization, so it is probable that our staining simply diffuses through enamel. This interpretation is supported by the fact that prisms are best distinguished with a TRITC staining rather than with a phalloidin‐TRITC one (used for staining cellular membranes), thereby suggesting that the size of the staining agent influences the staining's quality (a smaller agent diffusing more easily).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] In fact, dentin has been considered a semi-permeable membrane, in which fluid movement through its structure is mainly driven by the tubular channels and the nature of the solute/solvent ratio specified by the solute molecular size, geometrical form, and chemical affinity. 14,15 The permeation of different solutions into dentin has been studied; however, no model was found that could predict a PS and light permeation profile and its concentration throughout the diffusion process.…”
Section: Discussionmentioning
confidence: 99%